1978
DOI: 10.1111/j.1365-2621.1978.tb02299.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Spin Chilling and Freezing on Bacteria on Commercially Processed Turkeys

Abstract: A study was made of the effect of spin chilling and later freezing on possible spread of salmonellae and other bacteria on commercially processed turkeys in a federally inspected plant. Sixty-one turkeys were examined before and after spin chilling, after being "shell-frozen" in brine, after blast freezing and after being held in a freezer storage room. After spin chilling, levels of all organisms tested were reduced, and no salmonellae were recovered. Coagulase positive staphylococci persisted on turkeys duri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1982
1982
1995
1995

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…Some research has indicated that total microbial counts on carcasses are reduced by immersion chilling (Knoop et al, 1971;Brant, 1973;May, 1974;Thomson et al, 1975;Reddy et al, 1978). Other evidence indicates that chilling results in cross contamination of carcasses (Lillard, 1971(Lillard, , 1982.…”
Section: Introductionmentioning
confidence: 92%
“…Some research has indicated that total microbial counts on carcasses are reduced by immersion chilling (Knoop et al, 1971;Brant, 1973;May, 1974;Thomson et al, 1975;Reddy et al, 1978). Other evidence indicates that chilling results in cross contamination of carcasses (Lillard, 1971(Lillard, , 1982.…”
Section: Introductionmentioning
confidence: 92%